Pola Komunikasi Anak Dan Orang Tua Dalam Keluarga Broken Home Pada Kasus Perceraian - Aulia Cahyaning Ratri; Kadek Dristiana Dwivayani; Silviana Purwanti; Ziya Ibrizah (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study was motivated by the assumption that broken homes resulting from divorce always lead to poor communication between children and parents. In reality, every family has different communication dynamics depending on parenting styles, family values, and the interactions that develop in daily life. This study aims to analyze the communication patterns between children and parents in broken homes resulting from divorce among Communication Studies students at Mulawarman University using Family Communication Patterns Theory. The research focuses on two main dimensions: conversational orientation and conformity orientation. This study employs a descriptive qualitative approach using the case study method. Data were collected through in-depth interviews and documentation. The results indicate that there are differences in communication patterns between fathers and mothers, as well as differences in communication patterns among the various broken-home families. The communication pattern between IKS 1 and the mother showed low conversational orientation and moderate to low conformity, whereas the pattern between IKS 1 and the father could not be identified due to a breakdown in communication and interaction between them. The pattern between IKN 1 and the mother showed high conversational orientation and high conformity, while the pattern between IKN 1 and the father showed low conversational orientation and low conformity. This study concludes that a broken home does not necessarily determine poor family communication patterns, as communication quality is more influenced by parenting styles, family values, and the interactions established between parents and children.